Exosomes and the future of immunotherapy in pancreatic cancer - Batista, IA (2019)
Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease, associated with a late diagnosis and a five-year survival rate of 8%. Currently available treatments fall short in improving the survival and quality of life of PDAC patients. The only possible curative option is still the surgical resection of the tumor. Exosomes are extracellular vesicles secreted by cells that transport proteins, lipids, and nucleic acids to other cells, triggering phenotypic changes in the recipient cells. Tumor cells often secrete increased amounts of exosomes. Tumor exosomes are now accepted as important players in the remodeling of PDAC tumor stroma, particularly in the establishment of an immunosuppressive microenvironment. This has sparked the interest in their usefulness as mediators of immunomodulatory effects for the treatment of PDAC. In fact, exosomes are now under study to understand their potential as nanocarriers to stimulate an immune response against cancer. This review highlights the latest findings regarding the function of exosomes in tumor-driven immunomodulation, and the challenges and advantages associated with the use of these vesicles to potentiate immunotherapy in PDAC.